Learn more about

Refine search

Results (displaying matches 1-50 of 8719) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
363.a.43923.1 363.a \(y^2 + x^2y = 11x^5 - 13x^4 - 7x^3 + 10x^2 + x - 2\) $G_{3,3}$ 0
394.a.394.1 394.a \(y^2 + (x^3 + x)y = 2x^5 + x^4 - 12x^3 + 17x - 9\) $\mathrm{USp}(4)$ 0
461.a.461.1 461.a \(y^2 + x^3y = x^5 - 3x^3 + 3x - 2\) $\mathrm{USp}(4)$ 0
464.a.464.1 464.a \(y^2 + (x + 1)y = -x^6 - 2x^5 - 2x^4 - x^3\) $\mathrm{USp}(4)$ 0
464.a.29696.2 464.a \(y^2 + xy = 4x^5 + 33x^4 + 72x^3 + 16x^2 + x\) $\mathrm{USp}(4)$ 0
472.a.60416.1 472.a \(y^2 + (x + 1)y = 8x^5 + 5x^4 + 4x^3 + 2x^2\) $\mathrm{USp}(4)$ 0
597.a.597.1 597.a \(y^2 + y = x^5 + 2x^4 + 3x^3 + 2x^2 + x\) $\mathrm{USp}(4)$ 0
688.a.704512.1 688.a \(y^2 = 2x^5 + 4x^3 + x^2 + 2x + 1\) $\mathrm{USp}(4)$ 0
708.a.2832.1 708.a \(y^2 + (x^2 + x + 1)y = x^5\) $\mathrm{USp}(4)$ 0
726.a.1452.1 726.a \(y^2 + (x^2 + 1)y = 2x^5 + 2x^4 + 6x^3 - 2x^2 - x\) $G_{3,3}$ 0
784.c.614656.1 784.c \(y^2 = x^5 - 4x^4 - 13x^3 - 9x^2 - x\) $E_3$ 0
797.a.797.1 797.a \(y^2 + y = x^5 - x^4 + x^3\) $\mathrm{USp}(4)$ 0
832.a.832.1 832.a \(y^2 + (x^3 + x)y = x^5 - x^3 + x^2 + 2x - 1\) $\mathrm{USp}(4)$ 0
834.a.1668.1 834.a \(y^2 + (x^3 + 1)y = -x^2 + x - 1\) $\mathrm{USp}(4)$ 0
847.b.9317.1 847.b \(y^2 + (x^2 + 1)y = x^5 + 2x^4 - 3x^3 + 2x^2 - x\) $G_{3,3}$ 0
847.c.9317.1 847.c \(y^2 + (x^3 + x^2)y = x^4 + x^3 - x - 2\) $\mathrm{USp}(4)$ 0
862.b.862.1 862.b \(y^2 + (x^3 + x)y = -2x^4 + 3x^2 - x - 1\) $\mathrm{USp}(4)$ 0
997.a.997.1 997.a \(y^2 + xy = x^5 - 8x^4 + 16x^3 - x\) $\mathrm{USp}(4)$ 0
1042.a.1042.1 1042.a \(y^2 + (x^3 + x)y = -x^4 - x^3 - x^2 + 2x + 2\) $\mathrm{USp}(4)$ 0
1051.b.1051.2 1051.b \(y^2 + xy = x^5 + 8x^4 + 16x^3 + x\) $\mathrm{USp}(4)$ 0
1055.a.1055.1 1055.a \(y^2 + (x^3 + 1)y = -x^4 + x^2 - x - 1\) $\mathrm{USp}(4)$ 0
1069.a.1069.1 1069.a \(y^2 + (x^2 + x + 1)y = x^5 + x^3\) $\mathrm{USp}(4)$ 0
1077.b.1077.1 1077.b \(y^2 + x^3y = x^5 + x^4 - x - 2\) $\mathrm{USp}(4)$ 0
1104.a.17664.1 1104.a \(y^2 = x^5 - 2x^4 + 4x^3 - 4x^2 + 3x - 1\) $\mathrm{USp}(4)$ 0
1109.b.1109.1 1109.b \(y^2 + y = x^5 - x^4 - x^3 + x^2 + x\) $\mathrm{USp}(4)$ 0
1109.c.1109.1 1109.c \(y^2 + (x^3 + x)y = x^5 - 2x^3 - 2x^2 - 1\) $\mathrm{USp}(4)$ 0
1125.a.151875.1 1125.a \(y^2 + xy = 15x^5 + 50x^4 + 55x^3 + 22x^2 + 3x\) $G_{3,3}$ 0
1136.a.290816.1 1136.a \(y^2 + (x^3 + x^2)y = -5x^4 - 9x^3 + 25x^2 + 40x - 24\) $\mathrm{USp}(4)$ 0
1137.a.1137.1 1137.a \(y^2 + (x^2 + x + 1)y = x^5 + x^4 + x^3\) $\mathrm{USp}(4)$ 0
1147.a.35557.1 1147.a \(y^2 + xy = x^5 + 8x^4 + 18x^3 + 8x^2 + x\) $\mathrm{USp}(4)$ 0
1147.a.35557.2 1147.a \(y^2 + xy = x^5 + 6x^4 - 32x^2 + x\) $\mathrm{USp}(4)$ 0
1164.a.1164.1 1164.a \(y^2 + (x^3 + 1)y = -x^4 + x^2 - 1\) $\mathrm{USp}(4)$ 0
1197.a.10773.1 1197.a \(y^2 + (x^3 + x^2)y = -x^3 - x^2 - x + 2\) $\mathrm{USp}(4)$ 0
1216.a.1216.1 1216.a \(y^2 + (x + 1)y = -x^6 + x^4 - x^3 - x^2\) $\mathrm{USp}(4)$ 0
1225.a.6125.1 1225.a \(y^2 + (x^3 + x^2)y = 2x^3 + x^2 + x + 2\) $G_{3,3}$ 0
1231.a.1231.1 1231.a \(y^2 + (x^3 + 1)y = -x^4 + 2x^2 - x - 2\) $\mathrm{USp}(4)$ 0
1239.a.8673.1 1239.a \(y^2 + (x^2 + x + 1)y = -x^6 - x^2 - x\) $\mathrm{USp}(4)$ 0
1258.a.21386.1 1258.a \(y^2 + xy = x^5 + 4x^4 - 5x^3 - 4x^2 + 5x - 1\) $\mathrm{USp}(4)$ 0
1284.a.5136.1 1284.a \(y^2 + (x^3 + 1)y = -x^4 + x^2 - 2x + 1\) $\mathrm{USp}(4)$ 0
1285.a.1285.1 1285.a \(y^2 + y = x^5 - 2x^4 + 3x^3 - x\) $\mathrm{USp}(4)$ 0
1296.a.20736.1 1296.a \(y^2 = x^5 - x^4 - 3x^3 + 4x^2 - x\) $E_3$ 0
1309.a.9163.1 1309.a \(y^2 + (x^2 + 1)y = 7x^5 - x^4 - 5x^3 - x^2 + x\) $\mathrm{USp}(4)$ 0
1376.b.176128.1 1376.b \(y^2 + y = 4x^5 + 4x^4 + x^3 + 2x^2\) $\mathrm{USp}(4)$ 0
1408.a.180224.1 1408.a \(y^2 + (x^3 + x^2 + x + 1)y = x^4 - x^3 - 5x + 1\) $\mathrm{USp}(4)$ 0
1408.b.180224.1 1408.b \(y^2 = 2x^5 + 2x^4 + 4x^3 + 3x^2 + 2x + 1\) $\mathrm{USp}(4)$ 0
1408.b.720896.2 1408.b \(y^2 = x^5 + 2x^3 - 4x^2 + x\) $\mathrm{USp}(4)$ 0
1462.a.11696.1 1462.a \(y^2 + (x^3 + x)y = 2x^5 - 27x^3 - 38x^2 + 94x + 148\) $\mathrm{USp}(4)$ 0
1472.a.5888.1 1472.a \(y^2 = x^5 + x^4 - x^3 - 2x^2 - x\) $\mathrm{USp}(4)$ 0
1472.a.94208.1 1472.a \(y^2 = 4x^5 - 3x^4 - 4x^3 - x^2 + 7x - 3\) $\mathrm{USp}(4)$ 0
1473.a.1473.1 1473.a \(y^2 + (x^2 + x + 1)y = x^5 - x^4 - x\) $\mathrm{USp}(4)$ 0
Next

Download all search results for